Age and gender differences in anxiety and depression in cancer patients compared with the general population - Hinz, Andreas; Herzberg, Philipp Yorck; Lordick, Florian; Weis, Joachim; Faller, Hermann; Brähler, Elmar; Härter, Martin; Wegscheider, Karl; Geue, Kristina; Mehnert, Anja (European journal of cancer care, 2019)
Objective The aim of this study was to compare the levels of anxiety and depression in cancer patients with those of the general population, to examine age and gender differences in anxiety and depression, to analyse the impact of several socio‐demographic and clinical parameters on anxiety and depression, and to test the age and gender measurement invariance of the Hospital Anxiety and Depression Scale (HADS). Methods A sample of 3,785 German patients with cancer and a sample of 2,747 people of the German general population were examined using the HADS. Results Patients with cancer were more anxious but slightly less depressed than age‐ and gender‐matched individuals of the general population. Young patients with cancer were particularly affected by anxiety. Measurement invariance across gender and age could be established. For all analysed clinical variables, including tumour site, tumour stage, metastases, setting and Eastern Cooperative Oncology Group (ECOG) performance status we found no significant interaction effects with gender that exceeded the 5% significance criterion. Conclusion The HADS provides fair comparisons between age and gender groups. Gender differences in anxiety and depression can be generalised across the cancer sites and clinical subgroups. Young patients with cancer deserve special attention by the healthcare system.